Analysis Of The Influence Of Celebrity Endorsement On Purchase Intention With Brand Image As A Mediating Variable - Arya Darmawan; Ihawan Susila (SEAN Institute, 2024)
The aim of this research is to analyze and discuss the influence of celebrity attractiveness and credibility on purchase intention with the mediating variable of brand image of Samsung smartphones in the city of Surakarta. This study employs a quantitative approach using questionnaires for data collection. The study requires at least 50 respondents due to its two independent variables, but Chi-Square SEM testing suggests a sample size of 100 to 200 for optimal sensitivity. Therefore, the ideal number of respondents falls within the range of 100 to 200 individuals to meet the criteria. Non-probability sampling is utilized, targeting Samsung smartphone users aged approximately 17-35 in the Solo Raya area. Hypothesis testing and data analysis are carried out using Partial Least Square (PLS) with assistance from the SmartPLS 4 software tool. This study reveals several significant relationships: firstly, celebrity attractiveness has a considerable influence on brand image. Secondly, celebrity credibility also holds significant sway over brand image. Thirdly, brand image significantly affects purchase intention. Fourthly, celebrity attractiveness significantly impacts purchase intention. Fifthly, celebrity credibility positively affects purchase intention. Sixthly, attractiveness has a positive effect on purchase intention mediated by brand image. Seventhly, credibility similarly has a positive influence on purchase intention mediated by brand image.